Effectiveness of Snakehead Fish Extract on Tooth Extraction Wound Healing - HG, Afifah Ayuni; Syafruddin Ilyas; Olivia Avriyanti Hanafiah (HM Publisher, 2024)
Tooth extraction can cause open wound in the oral cavity, if not handled properly it can cause complications such as bleeding, infection and delayed wound healing. Wound healing is a biological process associated with tissue growth and regeneration. The wound healing process can be accelerated by administering chemicals that can affect the inflammatory, proliferative and remodeling phases. One of them is by giving snakehead fish extract. The extract contains albumin, copper and zinc which play an important role in the wound healing phase. The purpose of writing this review article is to explain the mechanism of snakehead fish extract in accelerating the healing of tooth extraction wounds. Several studies have revealed that snakehead fish extract affects pro-inflammatory cytokines in helping the wound healing process and significantly helps increase the number of fibroblast cells in tooth socket wounds, so that the healing process can take place more quickly. Based on this, it can be concluded that snakehead fish extract has the potential to accelerate the healing of tooth extraction wounds.